Midwest Collegiate Rocket Launch Competition: Raider Rocketry - Jensen, Benjamin Thomas (Proceedings of the Wisconsin Space Conference, 2017)
Student teams will be required to design, construct and fly a high-power â€œtrue scale modelâ€ of a current or retired rocket/missile system used somewhere in history. The rocket is required to use electronic deployment of the recovery parachute and a motor deployment as a backup. The apogee was limited to a range of 2500-3500 feet. The winner of the flight portion of the competition will be the team whose rocket completes a successful flight and whose rocket achieves an apogee closest to their predicted apogee, as recorded by a competition-provided flight recorder. Simulations and flight analysis were done using OpenRocket, a widely used and reliable software package for flight performance prediction. Several different launch conditions were modeled, with varying factors such as wind speed and launch angle. From this, we estimated that out rocket would reach an apogee of about 2600 feet. After launch, the recovered data indicated that the rocket reached an apogee of about 2900 feet.